Potret Kesenjangan Ekonomi Dalam Cerpen Langgam Urbana Karya Beni Setia, Cerpen Lelaki Ragi dan Perempuan Santan Karya Damhuri Muhammad, dan Cerpen Ngodop: Jabat Tangan Lima Puluh Juta Karya Nio Zaharani - Afifah, Fiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Economic disparities often still haunt life in all aspects. This study aims to find the potential for economic disparities that occur in the short stories Langgam Urbana by Beni Setia, Lelaki Ragi Dan Perempuan Santan by Damhuri Muhammad, and Ngodop: Jabat Tangan Lima Puluh Juta. The method used in this analysis is the descriptive analysis method and the type of qualitative analysis with a Marxist perspective. The data in this study were based on quotations, sentences, and even paragraphs that are related to the subject of economic disparities themselves. The use of research techniques carried out with reading and note-taking techniques, because the data used is in the form of text, and also because these two techniques can be evacuated or realized simultaneously. While for the analysis technique using a data analysis model, namely: 1) Presenting data, 2) Redacting data, and 3) Drawing conclusions. This study highlights in more detail the form of potential economic tension between city and village residents, rich people and poor people, and entrepreneurs and village religious teachers. Based on this research, it can be concluded that low-income communities are often easily persuaded, oppressed, and always live only with fantasy, but not infrequently also have what is pure—happiness—that cannot be bought with money.